Adherence to Therapeutic Regimens in Diabetic Patients in Tertiary Care Hospitals - Arif Mumtaz, Muhammad Ikram Shah, Ghazala Shaheen, Qaisar Ali Khan, Naseer Ahmad, Amir Khan (Pakistan Journal of Medical & Health Sciences, 2022)
For optimal glycemic control, diabetes patients must stick to their medication schedule. Poor adherence is a well-known issue that has a significant influence on health outcomes and healthcare expenses. As a result, this research was carried out to determine diabetic patients’ adherence to their recommended treatment regimen. Methodology: The study design used was a descriptive cross-sectional approach held in the Medicine Department of Jinnah Medical College Peshawar and DHQ & Teaching Hospital KDA Kohat for six months duration from April 2021 September 2021. The information was gathered via an interview using a structured questionnaire from 210 respondents who attended the medical OPD. The respondents were chosen by random sampling method. Descriptive and inferential statistics were used to conduct the investigation. Results: According to the outcomes of the research, there was strong follow-up adherence (58.1 percent). Medical treatment, diet restrictions, and exercise were all followed by 76.2 percent, 15.2 percent, and 10 percent of the population, respectively. Sexual orientation (p=0.03), educational level (p=0.001), occupational status (p=0.04), participation in diabetes counselling (p=0.001), and knowledge level (p0.001) were all shown to be linked with diet adherence. (p0.05) Exercise adherence was shown to be correlated with sex, educational level, attendance at diabetes counselling sessions, history of hospitalization, and degree of knowledge. Attending diabetes counselling was shown to be related with better medication adherence (p=0.03). Having diabetes for a long period of time, going to the doctor for follow-up visits often, and having a high level of knowledge were all linked with adherence to follow-up visits. Conclusion: The exercise and diet compliance among diabetes patients was much lower than compliance with the other components. As a result, it is advised that efforts be concentrated on education, Glycemic control might benefit greatly from better diet and exercise adherence.